Relaxação estrutural de vidros metassilicato de chumbo e dissilicato de lítio - Lancelotti, Ricardo Felipe (2021)
Glasses are thermodynamically unstable and spontaneously relax towards the supercooled liquid state. The relaxation time varies from seconds at temperatures above the glass transition to geological times at room temperature. Structural relaxation occurs because the unstable system tends to decrease its free energy. It is a process that depends on the thermal history, temperature of interest, and chemical composition of the glass. The glass properties change gradually with structure changes, which allows following the process through their measurements. In this work, structural relaxation of lead metasilicate and lithium disilicate glasses was studied by measuring the refractive index, glass transition temperature, and ionic conductivity over time of isothermal treatment. The Kohlrausch equation described well the experimental data. The characteristic relaxation time exponentially decreases, and the Kohlrausch exponent increases when the temperature increases. The average structural relaxation times were compared with that calculated by the Maxwell equation, which uses viscosity and shear modulus data. The results showed that the average structural relaxation time is slightly longer but close to that calculated via equilibrium viscosity. The relaxation curves are reproducible and cumulative with the time of isothermal heat treatment, but with different kinetics depending on the samples’ thermal history. When the three properties analyzed are compared, the beginning of relaxation is faster via ionic conductivity than via refractive index, which in turn, is faster than via glass transition temperature. However, it is the opposite for relaxing 99 % (revealing differences in the Kohlrausch exponent). Raman spectroscopy experiments did not identify significant changes after relaxation in the Qn species population, but they showed a small crystallization of the samples treated for relatively long periods below the glass transition.